Sharia Economic Law Analysis of Paylater Features in Online Marketplace Transactions - Abdul Fatakh; Eka Rosanti; Toto Suharto; Dila Annisa (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
The advancement of digital technology has significantly transformed buying and selling systems, particularly through online marketplace platforms. One notable innovation is the paylater payment scheme, which allows consumers to defer payments after completing transactions. While this method offers practical convenience, it raises critical concerns from the perspective of Sharia economic law, especially regarding the elements of riba (interest), gharar (uncertainty), and transactional justice. This study aims to analyze the implementation of paylater features in the Hijabequlla marketplace by examining their compliance with Sharia economic principles. Using a qualitative descriptive method, data were collected through observation, interviews, and literature review. The findings reveal that although the paylater scheme facilitates online purchases, its current implementation shows potential violations of Sharia provisions—particularly those outlined in the DSN-MUI Fatwa No. 1 of 2004 concerning interest-based transactions. The novelty of this research lies in its contextual analysis of a contemporary marketplace platform using the framework of Islamic economic law, offering insights into the alignment—or misalignment—between digital consumer financing and Sharia norms. The study concludes that a reconstruction of the paylater system is needed to ensure compliance with Islamic legal standards, thereby promoting fair and ethical digital transactions.Keywords: Marketplace; Paylater; DSN-MUI Fatwa; Digital Transactions; Sharia Economic Law.